Measurements of the leptonic branching fractions of the tau - Abreu, P; Adam, W; Adye, T; Adzic, P; Ajinenko, I; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; et al. (1999)
Data collected with the DELPHI detector from 1993 to 1995 combined with previous DELPHI results for data from 1991 and 1992 yield the branching fractions B(τ → evv̄) = (17.877 ± 0.109stat ± 0.110sys)% and B(τ → μvv̄) = (17.325 ± 0.095stat ± 0.077sys)%.